Strategi Peningkatan Pendapatan Nelayan Tradisional Di Desa Jalange, Kelurahan Mallawa, Kabupaten Barru, Sulawesi Selatan - Ryan Aryangga Ridwan; Muhammad Bibin; Damis Damis (Faculty of Science and Technology University Ibrahimy, 2026)
This study aims to analyze the socioeconomic conditions of traditional fishermen in Jalange Village, calculate the cost and income structure of fishing operations, and formulate development strategies using SWOT analysis. A descriptive quantitative approach was applied, involving the entire population of 30 fishermen as respondents. Data were collected through structured interviews, field observation, and documentation. The results show that fishermen conduct an average of 18 fishing trips per month with an average catch of 9 kg per trip and a selling price of IDR 28,000/kg. Total operational costs reached IDR 2,155,000 per month, while total revenue amounted to IDR 4,536,000, resulting in an average net income of IDR 2,381,000. The R/C Ratio of 2.10 indicates that fishing activities are economically feasible and profitable. SWOT analysis produced IFAS and EFAS scores of 3.10 and 2.80, placing the fishermen’s business in Quadrant I (growth strategy). Recommended strategies include increasing fishing trips during peak seasons, improving fishing gear efficiency, utilizing government support, and strengthening fishermen’s organizations. These findings contribute to the formulation of sustainable development strategies aimed at improving fishermen’s income and economic resilience. Keywords: fishermen income; operational cost; SWOT strategy.